Designing an Android-Based E-Marketplace System as Pekalongan Batik Trade Facility - Adib Hermawan; Dimas Kautsar Pratama; Bambang Dwinanto Priambodo (Systemic: Information System and Informatics Journal, 2019)
The development of online shop in this globalization era has progressed very rapidly, especially E-Marketplace. E-Marketplace is the most popular kind of online shop because of the guaranteed security by providing the intermediatery so customers do not need to be afraid to make a transaction without having to meet in person. International Batik Center (IBC) as one of the batik shopping areas in Pekalongan which provides place for more than 200 SMEs has a similar concept with E-Marketplace. IBC itself is not applying online business transactions at this moment so the marketing of SMEs products at IBC is limited in Pekalongan. To overcome this problem, an E-Marketplace system comprised of several sub systems will be designed. This research focuses on android-based sales sub-system. Design method used in this research is ICONIX Process. The purpose of this research is to build an android- based E-Marketplace system that can be used by customers as a medium to conduct online transactions. With E-Marketplace system, it is expected that all party in it, which are IBC, SMEs, and customers, will get a lot of benefits compared to the conventional market. In particular, this design is also expected to provide benefits for customers to simplify and speed up the transaction process.